2017
DOI: 10.1007/s40300-017-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

A new class of bivariate copulas: dependence measures and properties

Abstract: In this paper, we propose a new class of bivariate Farlie-Gumbel-Morgenstern (FGM) copula. This class includes some known extensions of FGM copulas. Some general formulas for well-known association measures of this class are obtained, and various properties of the proposed model are studied. The tail dependence range of the new class is 0 to 1, and its correlation range is more efficient. We apply some sub-families of the proposed new class to model a dataset of medical science to show the superiority of our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Nevertheless, the Farlie-Gumbel-Morgenstern copula has been shown to be somewhat limited since it does not allow the modeling of high dependencies. Indeed, its dependence parameter is θ ∈ [−1, 1], so its Spearman's rho and Kendall's tau are ρ θ = θ/3 ∈ [−1/3, 1/3] and τ θ = 2θ/9 ∈ [−2/9, 2/9], respectively (see, e.g., [7,8,37] and references therein). This limited range of dependence restricts the usefulness of this copula for modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the Farlie-Gumbel-Morgenstern copula has been shown to be somewhat limited since it does not allow the modeling of high dependencies. Indeed, its dependence parameter is θ ∈ [−1, 1], so its Spearman's rho and Kendall's tau are ρ θ = θ/3 ∈ [−1/3, 1/3] and τ θ = 2θ/9 ∈ [−2/9, 2/9], respectively (see, e.g., [7,8,37] and references therein). This limited range of dependence restricts the usefulness of this copula for modeling.…”
Section: Introductionmentioning
confidence: 99%
“…One of the advantages of the generalized FGM copula has wider range of correlation compared to regular FGM copula. According to Bekrizadeh and Jamshidi (2017), the estimated correlations based on the generalized FGM copula is closer to the actual correlation of the observed data compared to FGM copula. This conclusion is also shown in diabetic retinopathy study data.…”
Section: Introductionmentioning
confidence: 84%
“…In this paper, a mixture model is applied to analyze a bivariate censored data with different susceptibilities. A correlation coefficient is applied for cure rates and a generalized bivariate Farlie Gumbel Morgenstern (FGM) copula, proposed by Bekrizadeh and Jamshidi (2017), is applied for the association of bivariate failure times. As studied in Louzada et al (2013), it showed a weak dependence between tow lifetimes in the diabetic retinopathy study data.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, Amblard and Girard () proposed another extension, but its application is limited because of a singular component concentrated on the diagonal. Some other extensions of FGM coupla are discussed in Ahn () and Bekrizadeh and Jamshidi (). As mentioned before, it is a challenging problem to develop a bivariate life distribution with the flexibility that the correlation coefficient takes any value in the interval false[1,0false].…”
Section: Introductionmentioning
confidence: 99%